Ebook como tecnologia aliada ao cuidado paliativo do paciente idoso cirúrgico - Gomes, Felipe Clementino (2024)
Introduction: The ageing population has led to significant demographic and epidemiological changes, such as an increase in the incidence of diseases with no prospect of cure. In this context, the number of hospitalizations and surgical interventions exposes the elderly population to a disruptive experience that demands individualized understanding and resilience from the individual, in a scenario of reserved diagnosis. In this environment, palliative care emerges, an approach that, together with virtual learning tools, can help nurses to provide a continuum of living and dying well for the elderly, helping to transform the threatening experience into a source of meaning. Objective: To develop an ebook-type educational technology as a resource for implementing palliative care for elderly surgical patients. Method: A methodological study developed in three stages. In the first, a scoping review was carried out on Scopus, CINAHL, Web of Science, Embase, Lilacs, Medline, Google Scholar and ProQuest Dissertations, using the Joanna Briggs Institute method. The search returned 509 articles, of which 13 were chosen and processed in three stages, compiled in Rayyan® software and registered in the Open Science Framework (OSF). In the second stage, a qualitative study was carried out in a reference surgical hospitalization service with 16 nursing professionals, whose data was submitted to Bardin's content analysis. Finally, an ebook and a website were produced from the results obtained. Results: The most frequently encountered nursing actions concern the physical dimension, such as symptom control; the cultural dimension, with the challenges of palliative care in an environment with a high expectation of cure, as well as the dimension of communication as a basic tool of this approach. As for the qualitative findings, four categories emerged: 1) Communication as a link between nursing and the eligible elderly; 2) Barriers of the surgical routine; 3) Collective representations of palliative care and their implications and 4) The ideal of palliative care: suggestions for assistance. Conclusion: Palliative nursing care takes place empirically, focusing on physical and environmental aspects. Challenges arise in terms of care planning, the ethical dilemmas inherent in the surgical environment, as well as nurses' reluctance to be more open about the dying process. The technological product developed is an innovative and effective strategy, with animated elements, hyperlinks, web lessons and gamification strategies, in its digital book and webpage formats, which encourage the dissemination of information to professionals, a change in thinking and the promotion of a culture of compassionate, humanized and person-centred care.